Future Teachers’ Perception towards the Use of YouTube for Teaching-Learning Activities in Nigerian Basic Schools - Ogirima, Onivehu Adams; Tolulope, James Joy; Temitope, Sulaimon Jamiu (Mimbar Sekolah Dasar, 2021)
YouTube is one of the most utilized social media in the field of education. Nonetheless, the extent to which the diverse potentials of YouTube are being harnessed in the teaching-learning process is a function of the teachers’ perception. Hence, this study examined future teachers’ perception towards the use of YouTube for teaching-learning activities in Nigerian Basic Schools. The study employed descriptive survey method and 200 future teachers were selected using purposive sampling technique. The respondents filled to a questionnaire titled “Future Teachers’ Perception towards the Use of YouTube Questionnaire (FTPUYQ). The validity of the questionnaire was established by experts, while the test re-test reliability yielded a correlation coefficient of 0.79. The results revealed that future teachers had a high level of perception towards the use of YouTube in teaching-learning activities in Nigerian Basic Schools. It was found that there was no significant difference in the future teachers’ perception based on gender. Therefore, it was recommended that future teachers in Nigerian Basic Schools, should be exposed to various training and capacity building sessions on the procedure for creating, assessing, uploading and using YouTube videos to facilitate the success of the teaching-learning process.